PENERAPAN PENDEKATAN SAINTIFIK BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Adi Husen; Aflich Yusnita Fitrianna; Luvy Sylviana Zanthy (IKIP Siliwangi, 2022)
The purpose of this reseach is to analyze student learning outcomes on the material of a two variable system of linear equations by using a scientific approach assisted with learning videos. This reseach is classroom action reseach which is carried out in 2 cycles. In the first cycle of learning using a scientific approach without using learninh videos, while in the second cycle of learning using a scientific approach with the help of learning videos. The targets in this study were class VIII in one of the MTs in Bogor district. Collecting data based on the result of observations and student learning outcomes test sheets based on idicators of student competency achievement on the achievement of KKM scores by providing 5 item of description. From the test results it can be concluded that there is an increase in student learning outcomes in solving problems on the material of a two variable linear equations system in the form of a story. In the first cycle the students who completed the KKM were 50% while the students who completed the KKM in the second cycle were 90% of the total 20 student.